2017
DOI: 10.21037/tp.2017.05.04
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac screening to prevent sudden death in young athletes

Abstract: Sudden cardiac death (SCD) is a sudden and unexpected death caused by loss of heart of function. SCD may occur in any population, but when it occurs on the playing field in a young individual, communities worldwide are affected. Although these events are rare, media coverage of sudden cardiac arrests in young athletes have created the impression that these events are far more common than they appear. With a heightened awareness of SCD in young athletes, screening methods have been developed to try and prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
4
0
4
Order By: Relevance
“… 5 An important Italian study showed that mandatory ECG use reduced the annual incidence of cardiac SD by 90%. 291 The American Heart Association/American College of Cardiology question the cost-effectiveness of this strategy, the high rate of false-positive results, and the availability of qualified personnel to interpret the results. 292 On the other hand, the European Society of Cardiology recommends ECG for PPS.…”
Section: Basic Life Support For Athletesmentioning
confidence: 99%
“… 5 An important Italian study showed that mandatory ECG use reduced the annual incidence of cardiac SD by 90%. 291 The American Heart Association/American College of Cardiology question the cost-effectiveness of this strategy, the high rate of false-positive results, and the availability of qualified personnel to interpret the results. 292 On the other hand, the European Society of Cardiology recommends ECG for PPS.…”
Section: Basic Life Support For Athletesmentioning
confidence: 99%
“…Los afroamericanos y otras minorías fueron los más representados (5 veces más que los blancos) con HCM permaneciendo como la principal causa de MSC en esa población. Los autores recomiendan el uso de eco portátil antes del ECG debido a que este no es tan rentable ni recomendado a comparación del primero el cual muestra un futuro prometedor (9). Dijo Saadi y colaboradores realizaron un estudio de tipo cohorte retrospectiva utilizando datos de autopsia del Departamento de Medicina Legal de Monastir (Túnez).…”
Section: Resultsunclassified
“…Pese a que no era el objetivo principal, es importante resaltar que como método de prevención y detección de posibles factores que podrían desencadenar una MSC en adolescentes atletas, es recomendable el uso de electrocardiograma previo a a la realización de deportes siendo esto muy útil llegando a disminuir en hasta un 90 % los casos de MSC, a su vez el ecocardiograma portátil muestra un futuro 19 prometedor para la prevención de la MCS (9). Teniendo en cuanta la información previamente mencionada en las múltiples investigaciones se puede concluir que existe una relación entre la carga genética con relación a los parientes de primer grado y las cardiopatías congénitas, siendo estos los factores predisponentes a la MSC en adolescentes, siendo una patología en auge consumiendo cada vez más víctimas.…”
Section: Discussionunclassified
“…Some patients report palpitations, dizziness, or near syncope before SCD. Moreover, heart murmurs, heart rate or blood pressure irregularities, or physical stigmata of Marfan syndrome, might be evident [2,40]. Table 3 summarizes, ceratin findings that might be evident in patients' medical and family history [2,40].…”
Section: Premorbid Historymentioning
confidence: 99%